2020
DOI: 10.1097/hcr.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Adults With Wearable Cardioverter Defibrillators in the Post–Myocardial Infarction Period

Abstract: Purpose: Wearable cardioverter defibrillators (WCDs) provide lifesaving defibrillation and are equipped with accelerometers, capable of providing information on patient wear time and physical activity (PA). The purpose of this study was to report on patient PA while wearing a WCD. Methods: This study derived data from the WCD vendor in patients prescribed WCD post–myocardial infarction (MI) with left ventricular ejection fraction ≤35% in 2016. Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
0
17
0
2
Order By: Relevance
“…prescribed WCD post-acute MI in 2016, suggested that patients had significantly increased step counts over 13 weeks of WCD use (e.g.,~90 days). 21 Step counts increased from 3739 during the first week of wear to 6230 during last week of wear, representing a 67% increase in physical activity over a 90-day WCD prescription. Further analysis of the data suggested female patients wore the WCD significantly more time, but men completed significantly more steps (difference of 829/day).…”
Section: Normative Data From a Large Sample Of Patients (N = 1952)mentioning
confidence: 97%
See 4 more Smart Citations
“…prescribed WCD post-acute MI in 2016, suggested that patients had significantly increased step counts over 13 weeks of WCD use (e.g.,~90 days). 21 Step counts increased from 3739 during the first week of wear to 6230 during last week of wear, representing a 67% increase in physical activity over a 90-day WCD prescription. Further analysis of the data suggested female patients wore the WCD significantly more time, but men completed significantly more steps (difference of 829/day).…”
Section: Normative Data From a Large Sample Of Patients (N = 1952)mentioning
confidence: 97%
“…Additionally, older patients wore the device more time, but younger patients were more active. 21 Increases in patient age strongly predicted increases in device wear-time and decreases in physical activity after 40 years of age. 21 This study was SEARS ET AL.…”
Section: Normative Data From a Large Sample Of Patients (N = 1952)mentioning
confidence: 98%
See 3 more Smart Citations